2015
DOI: 10.1002/uog.14734
|View full text |Cite
|
Sign up to set email alerts
|

Fetal urine biochemistry at 13-23 weeks of gestation in lower urinary tract obstruction: criteria forin-uterotreatment

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 29 publications
0
40
0
1
Order By: Relevance
“…However, a question arises which is better: expectant approach at the expense of progressively deteriorating renal function [21], or early intervention with a high likelihood of normal renal function in the future. While the answer seems obvious from subjective parental perspective, also our objective findings seem to favour the early intervention since all survivors present with normal renal function at the age of 5-6 years.…”
Section: Discussionmentioning
confidence: 99%
“…However, a question arises which is better: expectant approach at the expense of progressively deteriorating renal function [21], or early intervention with a high likelihood of normal renal function in the future. While the answer seems obvious from subjective parental perspective, also our objective findings seem to favour the early intervention since all survivors present with normal renal function at the age of 5-6 years.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that biochemical analysis of fetal urine could provide valuable insights into prognosis for renal function, but there is no consensus regarding the best test or combination of tests. While good correlation has been observed between fetal serum β2M and postnatal serum creatinine after 24 weeks, fetal blood sampling is difficult to perform before 20 weeks [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Sodium levels in urine above 100 mmol/L have been found to indicate a condition threatening fetal life (usually either renal or pulmonary failure). 13,27 Beta 2-microglobulin is freely filtered by the normal fetal glomeruli and nearly in 100% reabsorbed in the proximal tubules, thus it can be useful as an indicator of fetal glomerular filtration rate (GFR). It also has a predictive value as to postnatal GFR.…”
Section: Assessment Of Fetal Renal Functionmentioning
confidence: 99%
“…Beta 2-microglobulin detected in the urine suggests an impairment in renal tubules function. 13,20,27 Other prognostic factors in fetal urine analysis, such as its specific gravity, osmolality, and the excreted volume have been defined by Glick et al 28 Tests assessing the beta 2-microglobulin in fetal urine and N-acetyl-beta-D-glucosaminidase (NAG) concentration in serum have been recently used to evaluate the degree of damage of renal parenchyma (their concentration is proportional to the extent of damage). The concentration of beta 2-microglobulin above 4 mg/L and cystatin C levels above 1 mg/L, and the NAG levels above 6 mg/dL are thought to be poor prognostic factors for postnatal renal function.…”
Section: Assessment Of Fetal Renal Functionmentioning
confidence: 99%
See 1 more Smart Citation